Analisis Produksi Industri Pengasapan Ikan Laut di Kabupaten Buton Provinsi Sulawesi Tenggara - Rahim, Manat (JURNAL KEBANGSAAN, 2018)
This study aims to analyze the factors affecting the production of smoked fish industry, analyzed the returns to scale the fish curing industry, and analyze the efficiency of input utilization rates in the industry of curing fish in the Buton regency. The data used is primary data were collected were colleted by interviewing respondents in a field survey. Number of respondents in this study of 50 people and is the census data is taken from the whole fish curing industry employers. Analysis method in the study regression with production function Cobb- Douglas, Estimation results indicate that the factors affecting the production of fish in the fumigation industry in Buton is raw fish, coconut shell and labor, which is statistically significant at alpha 5%. Furnace has a variable relationship is positive but not significant in influencing the production of smoked fish in the Buton regency. Thus, industrial production is largely determined by the curing of fish raw material raw fish, grilled coconut shell trap and labor used in the process of curing fish. Returns to scale (RTS) is 1.098. This means that in general the smoked fish business in Buton can still operate with an increased scale of business or follow the rules of Increasing returns to scale, but is close to constant conditions (constant returns to scale). While the analysis of efficiency of input utilization rates in industrial production of fish in Buton fumigation has not been efficient Keywords: Production Function, Fish Smoke Production.